DEVELOPING AN ANDROID APPLICATION ‘AMIYAH' OF ARABIC CONVERSATION FOR HAJJ AND UMRAH WITH KODULAR - Farida, Nilna Ulfatul; Firdaus, Mochammad (Arabi : Journal of Arabic Studies, 2022)
The development of the 'Amiyah' application is based on real conditions in the Arabic class for Hajj. The lack of Amiyah Arabic learning resources makes Arabic Language Education students experience difficulties when learning it. Therefore, to overcome the anxiety regarding minimal learning resources, researchers developed an Android based 'Amiyah' application that all groups, especially students, can use. This method applies development research (R&D) methods by adapting the Borg and Gall development model. The research instrument was an indirect closed questionnaire distributed via google form by personal chat. Samples were taken from as many as 30 students in the class. Quantitative and qualitative are used during data processing to provide easy to understand information. The results showed that the trial use of the 'Amiyah' application reached 85% with a very feasible interpretation. Thus, 'Amiyah' can be used as one of the learning media or learning media independently. ‘Amiyah' is available at the following link https://tinyurl.com/amiyahapk.